2020
DOI: 10.1001/jamanetworkopen.2020.11192
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastographic Results and Hypercoagulability Syndrome in Patients With Coronavirus Disease 2019 Who Are Critically Ill

Abstract: Author Contributions: Drs Mortus and Rosengart had full access to all of the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
197
4
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(216 citation statements)
references
References 7 publications
13
197
4
2
Order By: Relevance
“…Spieza. 8 This paralleled a report by Mortus et al13 who noted on thromboelastography (TEG), another viscoelastic tool, a significantly elevated maximal amplitude (MA, comparable to MCF in ROTEM) in all patients with two or more thrombotic events. Panigada et al 14 also noted shorter R and K values (comparable to CT and CFT, respectively)…”
supporting
confidence: 66%
“…Spieza. 8 This paralleled a report by Mortus et al13 who noted on thromboelastography (TEG), another viscoelastic tool, a significantly elevated maximal amplitude (MA, comparable to MCF in ROTEM) in all patients with two or more thrombotic events. Panigada et al 14 also noted shorter R and K values (comparable to CT and CFT, respectively)…”
supporting
confidence: 66%
“…While acknowledging that this is a speculation and that the dataset analyzed here is not proper to verify it, the question arises of whether individual predisposition cooperates with SARS-CoV-2-induced inflammation and endotheliopathy in causing VTE in COVID-19. Along these lines, it is notable that thromboelastographic hypercoagulability on admission was associated with higher thrombosis rates in critically ill COVID-19 patients, despite standard drug prophylaxis [ 17 ]. It should be also taken into account that therapies for COVID-19, such as ritonavir, tocilizumab, and hydroxychloroquine, may modulate the risk of VTE, both directly, via their effects on platelets, and indirectly, through their effects on the inflammatory system and pharmacokinetic interactions with antithrombotic medications [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Forty patients demonstrated acceleration of the propagation phase of blood clot formation (reduction of CFT in the INTEM and EXTEM) and a significantly higher clot strength (increase in MCF in the INTEM, EXTEM and FIBTEM) as compared to the normal range limits; this hypercoagulable state persists in the first days, but it decreases over time. Alike, Mortus et al enrolled 21 critically ill COVID-19 patients and reported that 19 of them presented with hypercoagulable TEG, defined as elevated fibrinogen activity greater than a 73° angle or MA more than 65mm on TEG with heparinase correction [ 17 ]. Innate TEG MA was significantly greater for the high thrombotic event rate group (≥2 thrombotic events) than the low event rate group (0-1 thrombotic events), while elevated MA was observed in 10 patients (100%) in the high thrombotic event rate group vs. five patients (45%) in the low event rate group.…”
Section: Evaluation Of Coagulopathy By Viscoelastic Methods In Sevmentioning
confidence: 99%
“…However, a correlation between ROTEM parameters and severity illness scores has not been reported [ 18 ]. It should be also pointed out that, in most cases, ICU COVID-19 patients have longer or normal CT/R values [ 12 , 13 , 17 , 18 , 19 ]. This is the only parameter not supporting the procoagulant profile of critically ill COVID-19 patients.…”
Section: Evaluation Of Coagulopathy By Viscoelastic Methods In Sevmentioning
confidence: 99%
See 1 more Smart Citation